TINJAUAN YURIDIS TERHADAP PIUTANG YANG DI ISTIMEWAKAN ( PRIVELEGE ) DALAM KUH PERDATA - Muhamad Saleh (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
AbstractFrom Article 1134 Paragraph (1) of the Civil Code it is clear that privileges or special receivables are due to law, it means that a right to the debtor's objects provided by the Civil Code law has limitedly specified or enumerated certain receivables including receivables which takes precedence in the settlement. As a consequence, the holder of such privilege or privilege shall have the right of priority in the settlement of his receivables compared to other creditors. Unlike the mortgage and the mortgages or guarantees of the material, the existence must be previously agreed by the parties, whereas the privilege is granted (determined) by law, that certain receivables which are due to the nature of the receivables shall take precedence in repayment if the debtor's property is sold.